The Effects of Subsidy Removal on the Escalation of Political Corruption in Nigeria - Sheyin, Adejoke Olabisi (NIU Journal of Social Sciences, 2018)
The historical study analyzed the effects of subsidy removal on the escalation of political corruption in Nigeria. Previous administrations in Nigeria were investigated with specific emphasis on President Sheu Shagari, General Ibrahim Babangida, Late General Sanni Abacha, General Abdulsalam Abubakar, President Olusegun Obasanjo and President Goodluck Jonathan administrations. The study revealed that none of these past governments judiciously made use of the gains realized from subsidy removal. President Shehu Shagari mismanaged US$16 billion in oil revenue between 1979 and 1983; General Ibrahim Babangida could neither account for the oil revenue accruable to the nation during the Gulf War nor could he make justification on the frivolous expenses on Better Life Programme of his administration. In the same vein, late General Sanni was found to have emptied the treasury by carting away huge amounts of money from the Central Bank. The democratically elected leaders, after 13years of the military, paid lip services to corruption and this increased the poverty level, with many Nigerians living on less than US$1 per day, while the supply of basic infrastructures in the country is in shambles. The study recommended that the Federal Government should rebuild citizens' confidence by cushioning the effects of the fuel subsidy removal and curb the excesses of corrupt public office holders, by bringing them to justice, irrespective of their status. Lastly, that the report of the House of Representative Ad-Hoc Committee on subsidy should be implemented by the Federal Government, to demonstrate its zero tolerance to corruption. Keywords: Subsidy, Political Corruption, MismanÂagement, Downstream Sector, and Poverty